Integrating Islamic Ethical Values Into Service Quality: Impact on Customer Satisfaction in the Halal Herbal Industry - Febrila, Lilia Gina; Aqidah, Nurul; Afrianty, Nonie (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2025)
Introduction: The rapid growth of the halal industry has intensified competition, requiring companies to focus not only on product quality but also on service quality. Customers evaluate services based on functionality, ethical standards, transparency, and compliance with Islamic values. Objective: This study examines the effect of Islamic service quality on customer satisfaction at Alfatih Business Center II of PT Herba Penawar Alwahida Indonesia (HPAI) in Bengkulu. Methods: An associative quantitative survey was conducted with 83 respondents selected via accidental sampling. Data were collected using a validated and reliable questionnaire (r > 0.2159; Cronbach's Alpha > 0.60) and analyzed using simple linear regression, t-tests, F-tests, and the coefficient of determination (R²). Results: Islamic service quality positively and significantly influences customer satisfaction, with the regression equation Y = 13.563 + 0.350X. The correlation coefficient (R = 0.696) indicates a strong relationship, and R² = 0.485 indicates that 48.5% of the variance in customer satisfaction is explained by service quality. Both t-test and F-test significance values were 0.000 (< 0.05), confirming statistical significance. Implications: Integrating Islamic ethics, transparency, and responsive service enhances customer satisfaction. In practice, improving employees' competencies in product communication, information clarity, and responsiveness to inquiries and complaints is essential for fostering customer loyalty in the halal herbal industry.